Exploring Physics Concepts in Songkok Recca Craft of the Bugis People in Bone South Sulawesi - Azhar Arsyad (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
Songkok Recca is a handicraft product of the Bugis Bone People of South Sulawesi and is an intangible cultural heritage in Indonesia. Songkok Recca contains various physics concepts that can be explored scientifically. Physics learning is often considered difficult for students, so there needs to be evaluation through the contextual and meaningful learning approach provided to help students form better understanding of physics concepts. This research aims to identify the physics concepts involved in the process of making Songkok Recca crafts and explore their potential in physics learning in a contextual manner. The method used in this research is a literature review research with data used as a source from various literature on the topic being studied. Based on the research that has been conducted, the physics concepts found in the Songkok Recca craft include force, pressure, work and energy, momentum and impulse, and equilibrium. The results of the research show that the Songkok Recca crafts of the Bugis Bone People of South Sulawesi can be used as a meaningful source of contextual physics learning. This research contributes to the development of ethnophysics by providing a comprehensive scientific interpretation of Songkok Recca crafts. In addition, the integration of Songkok Recca in physics learning is expected to improve the ability to understand concepts, physics literacy, and appreciation of local culture for students.